2022
DOI: 10.1126/sciadv.abn5466
|View full text |Cite
|
Sign up to set email alerts
|

Early diagenetic control on the enrichment and fractionation of rare earth elements in deep-sea sediments

Abstract: The rare earth elements and yttrium (REY) in bioapatite from deep-sea sediments are potential proxies for reconstructing paleoenvironmental conditions. However, the REY enrichment mechanism and the reliability of this tracer remain elusive because of the lack of key information from ambient pore water. Here, we report high-resolution geochemical data for pore water, bottom water, and bioapatite from deep-sea sites in the western Pacific. Our results reveal that the benthic flux of REY from the deep sea is less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…This study reports that the long‐term evolution of the depositional environment has been recorded in the multielemental geochemistry of pelagic clay and multivariate statistical techniques can serve as a promising tool for systematically deriving information from apparently uniform/massive clay facies. For seafloor mineral resource explorations, high‐dimensional geochemical data of pelagic clay enriched in REE called “REE‐rich mud” (Kato et al., 2011; Nakamura et al., 2015) and its constituents have been reported from oceans in recent years (Bi et al., 2021; Deng et al., 2022; Liao, Sun, Li, et al., 2019; Liao, Sun, Wu, et al., 2019; Liao et al., 2022; Menendez et al., 2017; Ren et al., 2022; Sa et al., 2018; Zhang et al., 2017; T. Zhou et al., 2020, 2021). The application of systematic statistical approaches to such a new, unexplored data stack of pelagic clay would provide incredible information on the geological history and/or critical metal‐ore genesis in the pelagic realm dominated by barren clay facies.…”
Section: Resultsmentioning
confidence: 99%
“…This study reports that the long‐term evolution of the depositional environment has been recorded in the multielemental geochemistry of pelagic clay and multivariate statistical techniques can serve as a promising tool for systematically deriving information from apparently uniform/massive clay facies. For seafloor mineral resource explorations, high‐dimensional geochemical data of pelagic clay enriched in REE called “REE‐rich mud” (Kato et al., 2011; Nakamura et al., 2015) and its constituents have been reported from oceans in recent years (Bi et al., 2021; Deng et al., 2022; Liao, Sun, Li, et al., 2019; Liao, Sun, Wu, et al., 2019; Liao et al., 2022; Menendez et al., 2017; Ren et al., 2022; Sa et al., 2018; Zhang et al., 2017; T. Zhou et al., 2020, 2021). The application of systematic statistical approaches to such a new, unexplored data stack of pelagic clay would provide incredible information on the geological history and/or critical metal‐ore genesis in the pelagic realm dominated by barren clay facies.…”
Section: Resultsmentioning
confidence: 99%
“…So far, the REY redistribution in pelagic sediments remains enigmatic. Deng et al (2022) proposed two REY release events during the early stages of diagenesis: (a) the first one occurs at/near the seawater-sediment interface, which might be due to organic matter degradation; (b) the second one occurs in a deeper layer whose trigger mechanism remains poorly constrained. As proven by our sequential leaching, Fe-Mn oxides are the most important REY carriers second to Ca-phosphate.…”
Section: Rey Accumulations In Different Burial Stagesmentioning
confidence: 99%
“…This might be attributed to the following factors: (a) the REY concentrations of the Ca-phosphate phase are so high that the REY removal from Fe-Mn (oxyhydr)oxides cannot significantly change its original signals; (b) The REY released by Fe-Mn (oxyhydr)oxides will be transported by the pore water. For example, previous studies from Deng et al (2022) and Abbott et al (2016) revealed the upward flux of REY from sediment to bottom seawater, which enables the REY scavenging by Ca-phosphate phases on the seawater-sediment interface (or within shallow sediment). Although the redistribution of REY from Fe-Mn oxides to Ca-phosphate during the burial process is extensively discussed, future studies should pay more attention to the deeper redox-changing layers and their potential communication with upper layers mediated by pore water.…”
Section: Rey Accumulations In Different Burial Stagesmentioning
confidence: 99%
“…1 REEs in porewater are thus altered by diagenetic release from sediments, adsorption onto particles, and incorporation into authigenic phases ( e.g. , nodules and phosphates); 4–7 meanwhile, fractionation would occur during the process due to the systematically changed properties based on the decreasing ionic radius from La to Lu. For example, REEs in porewater exists mainly in the form of carbonate complexes, while there is an increase in carbonate complexation strength with increasing atomic number, which leads to the preferential scavenging of light REEs (La–Gd) compared to heavy REEs (Tb–Lu) by particles.…”
Section: Introductionmentioning
confidence: 99%
“…8 In particular, with the employment of the depth profile of REEs or normalized REEs pattern, the enrichment or depletion of REEs in porewater can be easily recognized, 3,7 which could provide important information on the diagenetic processes, sedimentary environment, sources of trace elements to the ocean, and the enrichment mechanism of REEs in marine sediments. However, only a few studies on porewater REEs 3–7,9–13 have been reported because of analytical challenges. Similar to REEs in seawater, these elements exist in porewater at a concentration of pg mL −1 level and with a complex matrix of high salinity (about 35 g kg −1 ).…”
Section: Introductionmentioning
confidence: 99%